A comparative analysis of selected attributes of four brands of corned beef - Tan, Imelda
The scope of this study is the chemical analysis and sensory evaluation of four random brands of corned beef. The moisture, fat, protein, cereal, TVP and residual nitrite contents of each of the four brands were determined. Sensory evaluation was conducted for color, over-all flavor, starchy flavor, texture, and general acceptability. The study showed that compared to the composition of typical processed meats as prescribed by Price at.al., 1971, moisture content of all brands fall below the set standard. Brand C and D were above while Brand A and B were below the prescribed limit of protein content. Fat contents of all brands were higher than the prescribed limits. Residual nitrite of all brands are far below the 200 ppm maximum limit. Cereal and TVP were not present. Statistical analysis showed significant differences between brands in color, starchy flavor an general acceptability.